A novel recombinant antibody specific to full-length stromal derived factor-1 for potential application in biomarker studies. - Daniel I Bromage; Stasa Taferner; Mahesh Pillai; Derek M Yellon; Sean M Davidson (PLoS ONE)
Background Stromal derived factor-1α (SDF-1α/CXCL12) is a chemokine that is up-regulated in diseases characterised by tissue hypoxia, including myocardial infarction, ischaemic cardiomyopathy and remote ischaemic conditioning (RIC), a technique of cyclical, non-injurious ischaemia applied remote from the heart that protects the heat from lethal ischaemia-reperfusion injury. Accordingly, there is considerable interest in SDF-1α as a potential biomarker of such conditions. However, SDF-1α is rapidly degraded and inactivated by dipeptidyl peptidase 4 and other peptidases, and the kinetics of intact SDF-1α remain unknown. Methods & results To facilitate investigation of full-length SDF-1α we established an ELISA using a novel recombinant human antibody we developed called HCI.SDF1. HCI.SDF1 is specific to the N-terminal sequence of all isoforms of SDF-1 and has a comparable KD to commercially available antibodies. Together with a detection antibody specific to the α-isoform, HCI.SDF1 was used to specifically quantify full-length SDF-1α in blood for the first time. Using RIC applied to the hind limb of Sprague-Dawley rats or the arms of healthy human volunteers, we demonstrate an increase in SDF-1α using a commercially available antibody, as previously reported, but an unexpected decrease in full-length SDF-1α after RIC in both species. Conclusions We report for the first time the development of a novel recombinant antibody specific to full-length SDF-1. Applied to RIC, we demonstrate a significant decrease in SDF-1α that is at odds with the literature and suggests a need to investigate the kinetics of full-length SDF-1α in conditions characterised by tissue hypoxia.